Women Carrying Goods at Namlea Market in Family Economic Empowerment - Nawawi, Mansyur; Umanialo, Rosita; Lisaholit, Syafa; Umanailo, Muhamad Chairul Basrun (ARISTO, 2025)
Female workers are female workers at Namlea Market, Buru Regency. As providers of labor services, they will transport and deliver every item consumers purchase to the location where they shop. Work complete of risks and exposure to health hazards does not prevent them from continuing their activities, and the actions taken become women's existence in meeting the economic needs of their families. This study is a qualitative study designed to describe the role of female workers in meeting household needs. The research locations are Karang Jaya Village, Namlea Market, and Namlea Terminal, considering the scope of the informant's activities. The analysis technique used is based on the concept of Miles and Huberman, which states that qualitative data analysis must be carried out interactively and continuously. The study results indicate that female workers are the central pillar in household livelihoods, and efforts to meet household needs are prioritized over physical strength without considering its health risks. In addition, to cover the shortage of needs, female workers work outside their primary jobs, such as cleaning shops, providing cleaning services, and processing agricultural products. Recommendations for stakeholders in efforts to improve the welfare of women who carry goods in the Namlea market include providing access to affordable health insurance, adequate rest facilities in the workplace, and micro-business capital assistance to increase household income.